Apatite minerals derived from collagen phosphorylation modification induce the hierarchical intrafibrillar mineralization of collagen fibers. Issue 11 (20th June 2019) - Du, Tianming; Niu, Xufeng; Hou, Sen; Li, Zhengwei; Li, Ping; Fan, Yubo
Abstract: Collagen is the critical organic component of bone matrix, which is the template for bone biomineralization. Phosphorylation modification of collagen plays an important role in the process of biomineralization in vivo, but its mechanism on in vitro biomimetic mineralization of bone matrix remains unclear at the molecular level. Sodium tripolyphosphate is used to phosphorylate collagen in this study and new phosphate groups appear on collagen fibrils after phosphorylation modification. The chelating amount of calcium is improved linearly with increasing the phosphorylation degree of collagen fibrils, which demonstrates that the introduced phosphate groups serve as new nucleation sites and participate in the formation of apatite minerals inside the collagen fibers. Stabilized nanosized amorphous calcium phosphate by polyacrylic acid can also permeate into collagen fibers and further transform into another layer of hydroxyapatite minerals. Both layers of apatite minerals eventually induce the formation of hierarchical intrafibrillar mineralization structure within the phosphorylated collagen fibers. The present research enriches the previous biomineralization mechanism of bone matrix, provides a facile strategy for biomimetic mineralization of collagen, and offers the basis for future investigation of the advanced bone substitute materials.